Response of cardamom (Elettaria cardamomum Maton) to NPK under uniform shade - CHANDRAPPA, B JAGANNATH, S M SHANTHAVEERABHADRAIAH, H M (Journal of Spices and Aromatic Crops, 1997)
Experiments conducted during 1987-94 at Mudigere (Karnataka, India) to study the response of different levels of N, P and K on the yield of cardamom (Elettaria cardamomum) under uniform shade indicated that increasing N up to 100 kg/ha resulted in a significant increase in capsule yield. Application of P at 50 kg/ha had a positive effect on yield; further increase of P up to 100 kg did not give significant results. In the case of K, significant increase in yield was observed up to 100 kg/ha. The effect of NPK levels on yield component factors such as suckers and panicles varied from year to year.